Cloud Computing As an Emerging Paradigm in E-Learning: SWOT Analysis - M. Tak, Dr. Reena; Upadhyay, Dr. Atul (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
E-learning, also known as CBT (Computer-Based Training), IBT (Internet-Based Training) or WBT (Web-Based Training),refers to electronic learning where electronic devices like computer and technology like internet and its services play an important role in teaching and learning process. The content is delivered digitally with learning support and other services to the learner. To successfully implement this process, hi -tech devices and technological advancements need to be accommodated in due course. Huge investments in establishing all these resources became a bottleneck for medium and small scale institutions in India. Cloud computing emerged as a solution as it provide almost any service as a shared and pay per use resource. It provides resources and capabilities of information technology via services offered by cloud service provider through internet. In this paper, the authors study the e-learning scenario and cloud computing as a solution provider. The authors also did a quick Strength, Weakness, opportunity, Threat (SWOT) analysis for the above mentioned context.